Impact Of Firm Specific Factors On Capital Structure Decision: An Empirical Study Of Albanian Firms. - Çekrezi, Anila (European Journal of Sustainable Development, 2013)
This paper attempts to explore the impact of firm specific factors on capital structuredecision for a sample of 65 non- listed firms, which operate in Albania, over the period2008-2011.In this paper are used three capital structure measures ; short –term debt tototal assets (STDA), long- term debt to total assets (LTDA) and total debt to total assets(TDTA) as dependent variables and four dependent variables: tangibility(TANG),liquidity (LIQ), profitability(ROA=return on assets) and size (SIZE). The investigationuses panel data procedure and the data are taken from balance sheets and include onlyaccounting measures on the firm’s leverage. This study found that tangibility (the ratio offixed assets to total assets), liquidity (the ratio of current assets to current liabilities)profitability (the ratio of earnings after taxes to total assets) and size (natural logarithm oftotal assets) have a significant impact on leverage. Also empirical evidence reveals asignificant negative relation of ROA to leverage and a significant positive relation ofSIZE to leverage. And the second objective of this study is to identify the impact ofindustry classification on firm’s leverage, using a dummy variable for the trade sector. Soone of the hypothesis tested is if financial leverage is independent of industryclassification. Results reveal that long term debt to total assets and total debt to totalassets ratios are significantly different across Albanian industries.